Pengaruh Soft Skill Terhadap Kesiapan Kerja Di Era Society 5.0 Pada Mahasiswa Program Studi Manajemen Fakultas Ekonomi dan Bisnis Unismuh Makassar - Padila Salsa, Peby; Nurbaya, Sitti; Nasrullah (Paradoks : Jurnal Ilmu Ekonomi, 2025)
This type of research is quantitative research with the aim of knowing the Effect of Soft Skills on Work Readiness in the Era of Society 5.0 in Management Study Program Students, Faculty of Economics and Business, Unismuh Makassar. The sample in this study amounted to 76 people. The type of data used in this study is quantitative data obtained from questionnaires distributed and related to the problem under study. Data collection was carried out by observation and distribution of questionnaires. The data sources used in data collection are primary data and secondary data. Data analysis using Simple Linear Regression and processed through the Statistical Package For The Social Science (SPSS) version 25 application. The results showed that soft skills have a positive and significant effect on work readiness in the era of society 5.0 in Management study program students at the Faculty of Economics and Business, Unismuh Makassar. This shows that mastery of soft skills is a crucial factor in increasing students' work readiness to face the challenges and needs of the world of work in the era of society 5.0. Keywords: Soft skills, work readiness.